Implementing Jigsaw To Improve The Ability Of The Eighth Grade Students Of Smp Plus Darussalam In Writing Narrative - Adib Ahmada (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2015)
Based on the finding of the preliminary study held at SMP Plus Darussalam 8 students or 26.7 % got score more than 70 in writing narrative test. The researcher proposed jigsaw to solve the problem. Jigsaw is strategy in which the learners are doing activity in home group and expert group. The objective of the study is to improve the students’ ability in writing narrative through jigsaw. This study was designed for collaborative classroom action research in which the researcher (acted as teacher) and the collaborator (acted as the observer) worked together on the procedures of the study, namely: planning, implementing the plan, observing the action, and reflecting the result of the acti on. The subjects of the study were 30 students of the eighth grade of SMP Plus Darussalam. This research was done in two cycles . Each cycles consisted of two meetings in which teaching learning using jigsaw was done. The data of this research are obtained through (1) observation checklist, to obtain information about the researcher’s and the students’ activities and performance during the implementation of jigsaw, (2) field notes, to note the data beyond the coverage of the observation checklist, and (3) test, to identify whether the students make progress in writing narrative. The research shows that the implementation of jigsaw in the teaching learning activity can improve the students’ writing narrative. It can be identified that after the implementation of the action there is an improvement on the number of the students who got score greater than 70.